Design and test of 2ZYM-2 potted vegetable seedlings transplanting machine - Jin, Xin; Cheng, Qun; Zhao, Bo; Ji, Jiangtao; Li, Mingyong (International Journal of Agricultural and Biological Engineering, 2020)
In order to improve the efficiency and quality of transplanting vegetables in dry land, based on the seedling technology, transplanting effect and analysis of the planting process, a potted vegetable seedlings transplanting machine was designed. It mainly comprised rotary disc type feeding mechanism, five-bar duckbill type planting mechanism (simulated duckbill mechanism, disc cam, connecting rod, crank, fork, cable) and power transmission system. Based on the physical parameters of the seedlings and design requirements, it was determined that the diameter of the duckbill was D=90 mm, the opening and closing angle was 25°, and the taper angle was 17°. A test bench with adjustable parameters was built by analyzing the structure of the planting mechanism and the motion of the working process. The digital speckle technique was used to optimize the parameters, so that the length of the crankshaft Ι was S1=100 mm, the length of the crankshaft ΙΙ was S2= 80 mm, the length of the connecting rod Ι was S3=140 mm, the length of the connecting rod ΙΙ was S4=260 mm, the length of rod to connecting the rack was S6=314 mm, and the height of planting track was H=450 mm. According to the above parameters and the control requirements of the duckbill mechanism, the cam stroke was determined to be S=15 mm. And the initial phase difference between the two cams was 180°. The experiment was carried out with pepper seedlings as transplanting objects. The results showed that when the planting frequency was 50-70 plants/min, the seedling upright rate was 93%-91.1%, the planting depth qualified rate was 96%-92%. The leakage rate was 0-0.26%, the variation coefficient of plant spacing was 0.37%-0.67%, the injury rate was 0%, and the mechanical damage degree of the mining surface was 2.43-3.77 mm/m2. The machine can effectively improve the quality of transplanting, which can meet the production needs and design requirements of the mechanism.Keywords: seedling transplanting, planting mechanism, digital speckle, parameter optimization, test analysisDOI: 10.25165/j.ijabe.20201301.5494Citation: Jin X, Cheng Q, Zhao B, Ji J T, Li M Y. Design and test of 2ZYM-2 potted vegetable seedlings transplanting machine. Int J Agric & Biol Eng, 2020; 13(1): 101–110.